2022
DOI: 10.1186/s12955-022-01938-6
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties and responsiveness of the EQ-5D-Y-5L compared to the EQ-5D-Y-3L in children and adolescents receiving acute orthopaedic care

Abstract: Objective The aim of this study is a head-to-head comparison of the instrument performance and responsiveness of the EQ-5D-Y-3L and the expanded English version of the EQ-5D-Y-5L in children/adolescents receiving acute orthopaedic management in South Africa. Methods Children/adolescents aged 8–15 years completed the EQ-5D-Y-5L, EQ-5D-Y-3L, self-rated health (SRH) question and PedsQL at baseline. The EQ-5D-Y-5L, EQ-5D-Y-3L and SRH question were repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Moreover, previous studies have indicated the low associations between EQ-5D-Y-3L dimension and PedsQL subscales scores in a cross-sectional fashion, such as in the pediatric orthopedic [27] and general population in Japan [25]. We found evident correlations (Spearman ρ > 0.3) between longitudinal changes in VAS of EQ-5D-Y and PedsQL for total score, emotional and social subscales (all Spearman ρ = 0.32, all p < 0.005), whereas no correlations (Spearman ρ < 0.3) appeared between each domain of EQ-5D-Y and PedsQL scores.…”
Section: Summary Of Ndingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, previous studies have indicated the low associations between EQ-5D-Y-3L dimension and PedsQL subscales scores in a cross-sectional fashion, such as in the pediatric orthopedic [27] and general population in Japan [25]. We found evident correlations (Spearman ρ > 0.3) between longitudinal changes in VAS of EQ-5D-Y and PedsQL for total score, emotional and social subscales (all Spearman ρ = 0.32, all p < 0.005), whereas no correlations (Spearman ρ < 0.3) appeared between each domain of EQ-5D-Y and PedsQL scores.…”
Section: Summary Of Ndingsmentioning
confidence: 97%
“…Alternatively, EQ-5D-Y was based on 3-level ordinal response choices, which may not be ideal for measuring changes in children's HRQOL. For instance, Verstraete et al indicated that EQ-5D-Y-5L can reduce the ceiling effect and had greater discriminate ability than EQ-5D-Y-3L on pain/discomfort and doing usual activity domains in the pediatric orthopedic population in South Africa [27].…”
Section: Summary Of Ndingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kruskal–Wallis H test was computed for comparison of VAS scores between groups. It was expected that children with an orthopaedic condition and those with a functional disability would report more problems in the Mobility dimension compared to other groups [ 25 , 27 , 39 ]. It was also anticipated that children with an orthopaedic condition (being more acutely ill), would report more problems with Usual Activities and Pain or Discomfort [ 27 , 40 ].…”
Section: Instrumentsmentioning
confidence: 99%
“…An observational, analytical cohort study was conducted with the Y-5L, Y-3L, PedsQL and SRH question. A headto-head comparison of the Y-5L and Y-3L instrument performance is presented elsewhere [18,21].…”
Section: Study Design and Participantsmentioning
confidence: 99%